Transcription factor TFIIB and the vitamin D receptor cooperatively activate ligand-dependent transcription. - Blanco, J C (1995)
The active metabolite of vitamin D, 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], regulates gene transcription through binding to the vitamin D receptor (VDR), a member of the nuclear hormone receptor superfamily. Sequence-specific transcription factors, including nuclear hormone receptors, are thought to interact with the basal transcription complex to regulate transcription. In glutathione S-transferase fusion-based protein-protein binding assays we found that VDR specifically binds to TFIIB, a component of the basal complex, and that the interaction requires select domains of each protein. To assess the functional significance of this interaction, transfection assays were performed with a 1,25(OH)2D3-responsive reporter construct. In P19 embryonal carcinoma cells cotransfection of VDR and TFIIB cooperatively activated reporter transcription, while each factor alone gave very low to no activation. This activation was dependent on 1,25(OH)2D3 and the dose of TFIIB and VDR transfected, demonstrating that a nuclear hormone receptor functionally interacts with TFIIB in vivo. In contrast, transfection of NIH 3T3 cells generated strong reporter activation by 1,25(OH)2D3 in the presence of VDR alone, and cotransfection of TFIIB led to specific dose-dependent repression of reporter activity. Taken together, these results indicate that TFIIB-nuclear hormone receptor interaction plays a critical role in ligand-dependent transcription, which is apparently modulated by a cell-type-specific accessory factor.